IMPROVING INTERNAL AUDIT QUALITY THROUGH SELF EFFICACY AND PROFESSIONAL ETHICS WITH TOP MANAGEMENT SUPPORT AS A MODERATION VARIABLE - Tuti Dharmawati; Asri Ady Bakri; Endah Prawesti Ningrum; Mahdi Mahdi; Nicholas Renaldo (International Journal of Economics, Business and Accounting Research (IJEBAR), 2023)
This research aims to empirically analyze Internal Audit Quality Improvement through Self Efficacy and Professional Ethics with Top Management Support as a Moderating Variable. The population in this study are all auditors who work for state-owned banks in the DKI Jakarta area. Sampling was carried out by using purposive sampling method and the number of samples was 82 respondents. The primary data collection method used is the questionnaire method. Data were analyzed using the Moderated Regression Analysis (MRA) technique. The research results show that 1) Self efficacy has a significant effect on audit quality, 2) Professional ethics has a significant effect on audit quality, 3) Self efficacy and professional ethics have a significant effect on audit quality, 4) Top management support moderates the relationship between self efficacy and audit quality, and 5) Top management support moderates the relationship between professional ethics and audit quality . These findings reveal that if a company wants to improve the quality of internal audits, the company must also improve self-efficacy, professional ethics and top management support.